LAJU KOROSI DALAM LARUTAN ASAM SULFAT DENGAN MENGGUNAKAN INHIBITOR ASAM OKSALAT - Rizki, Diah (CHEMISTRY PROGRESS, 2008)
The objectives of this research were study the effect of addition oxalat acid on inhibiting of stainless steelcorrosion in sulfuric acid solution. The stainless steel sample sieved and macerated in sulfuric acidsolution with concentration 0.05 M for 24, 48 and 72 hours. The corrosion rate are evaluated with Asdimof method. The result showed that corrosion rate of stainless steel in sulfuric acid for 72 hour is 0,1309mg/ cm2jam. The corrotion rate rate of stainless steel in sulfuric acid with addition axalat acid inhibitor withconcentracion 1.10-3M , 2.10-3M , 3.10-3M , 4.10-3M for 72 jam were 0,0157 , 0,0188, 0,017 , and 0,0165mg/cm2hour. . It is concluded thatoxalat acid having inhibition effect on stainless steel corrosionÂ Keywords: oxalate acid, stainless steel, corrosion, sulphuric acid